Otolaryngologist and pediatric oncologist perspectives on the role of fine needle aspiration in diagnosing pediatric head and neck masses. (June 2019) - Roth, L.; Moerdler, S.; Weiser, D.; Douglas, L.; Gill, J.; Roth, M.
Abstract: Objective: To determine how otolaryngologists and pediatric oncologists differ in their initial approach to diagnosing head and neck masses in children and adolescents. Methods: We designed an electronic 28-question survey consisting of 4 clinical cases and one referral case varying by patient age, history, and physical exam findings. The survey was sent anonymously to pediatric oncologists and otolaryngologists at institutions in the United States and Canada. Results: Two hundred and thirty one pediatric oncologists (29.4%) and 87 otolaryngologists (39.5%) completed the survey. Otolaryngologists were significantly more likely to recommend performing an FNA than oncologists in all four cases; less than 7% of pediatric oncologists recommended FNA for head and neck mass evaluation. Of providers who recommended FNA, otolaryngologists were more likely to do so because of diagnostic yield when compared to pediatric oncologists. However, when referred a patient with an FNA demonstrating non-Hodgkin lymphoma, the majority of pediatric oncologists (73.6%) and otolaryngologists (78.7%) would complete the staging work-up and begin treatment. If the same patient was referred with an FNA that demonstrated non-specific inflammation, most oncologists (91.0%) and otolaryngologists (94.4%) would biopsy the mass. Conclusion: Otolaryngologists and pediatric oncologists differ in their initial approach to diagnosing head and neck masses in children, yet they both would recommend treating a patient with a positive FNA. This highlights important differences in the diagnostic process depending on which provider sees the patient first. Further studies assessing the sensitivity and specificity are needed to determine the true diagnostic yield of FNAs in the assessment of head and neck masses in children and adolescents, especially with increasing need for molecular and genomic profiling.